The Influence of Colors in the Interior on the Mood and Behavior of People and Children (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Colours have a strong influence on a person's psyche and behavior. Not only can it be painted with color, but it can spoil the interior of the building. It is necessary to work with colors very carefully, in which it is necessary to get acquainted with natural colors and color composition at will.